2013
DOI: 10.5336/medsci.2012-33360
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Staphylococcus and Enterococcus Isolates to Linezolid, Daptomycin, Teicoplanin and Fusidic Acid

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Koagülaz negatif stafilokoklar (KNS), Staphylococcus aureus (S. aureus) ve enterokoklarda glikopeptid direnci giderek artmaktadır. Bu çalışmanın amacı, hastane kaynaklı metisiline dirençli stafilokok ve enterokok izolatlarının son yıllarda kullanıma giren linezolid ve daptomisin ile uzun zamandır kullanılan teikoplanin ve fusidik asit (enterokoklar hariç) için in vitro duyarlılığını araştırmaktır. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Hastane kaynaklı toplam 172 izo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Dizbay et al [13] investigated linezolid sensitivity in 120 MRSA strains by disk diffusion method and no resistant strain was detected. In the study of Kanan et al, [20] the MIC ranges of linezolid were 1-4 μg/ml in MRSA, 0.5-2 μg/ml in MRCoNS 0.25-1 μg/ml, 1-2 μg/ml in E. fecalis, and 1-4 μg/ml in E. faecium Ertem et al [29] did not report linezolid resistance between 2008 and 2009 in 120 hospital-acquired staphylococci strains. Ağalar et al [30] found linezolid resistance as 3% in 276 staphylococci strains resistant to methicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Dizbay et al [13] investigated linezolid sensitivity in 120 MRSA strains by disk diffusion method and no resistant strain was detected. In the study of Kanan et al, [20] the MIC ranges of linezolid were 1-4 μg/ml in MRSA, 0.5-2 μg/ml in MRCoNS 0.25-1 μg/ml, 1-2 μg/ml in E. fecalis, and 1-4 μg/ml in E. faecium Ertem et al [29] did not report linezolid resistance between 2008 and 2009 in 120 hospital-acquired staphylococci strains. Ağalar et al [30] found linezolid resistance as 3% in 276 staphylococci strains resistant to methicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Ertem ve ark. (28) ile Ağuş ve ark. (29) da çalışmalarında stafilokok izolatlarında linezolide direnç belirlemediklerini bildirmişlerdir.…”
Section: Gereç Ve Yöntemunclassified